2014
DOI: 10.1371/journal.pone.0094722
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Cardiac Intercalated Disk during Pre- and Postnatal Development of the Human Heart

Abstract: BackgroundIn cardiac muscle, the intercalated disk (ID) at the longitudinal cell-edges of cardiomyocytes provides as a macromolecular infrastructure that integrates mechanical and electrical coupling within the heart. Pathophysiological disturbance in composition of this complex is well known to trigger cardiac arrhythmias and pump failure. The mechanisms underlying assembly of this important cellular domain in human heart is currently unknown.MethodsWe collected 18 specimens from individuals that died from no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 39 publications
6
88
0
Order By: Relevance
“…38 This is similar to human hearts where redistribution of Cx43 from the entire cell surface to the intercalated disc takes also place during postnatal development and continues to ≈7 years of age. 39,40 Consistent with this we observed punctate staining of Cx43 on the ventricular cardiomyocyte surface in newborn control and Cx43+/E42K hearts with no obvious differences in expression or localization between the genotypes (Figure 4). In contrast to Cx43E42K-mutated mouse hearts, in the human Cx43E42K victim's heart a patchy Cx43 protein expression pattern was reported suggesting 20 It is possible that the patchy Cx43 staining pattern observed in the myocardial tissue from the Cx43E42K victim results from poor quality of necropsy tissue.…”
Section: Discussionsupporting
confidence: 82%
“…38 This is similar to human hearts where redistribution of Cx43 from the entire cell surface to the intercalated disc takes also place during postnatal development and continues to ≈7 years of age. 39,40 Consistent with this we observed punctate staining of Cx43 on the ventricular cardiomyocyte surface in newborn control and Cx43+/E42K hearts with no obvious differences in expression or localization between the genotypes (Figure 4). In contrast to Cx43E42K-mutated mouse hearts, in the human Cx43E42K victim's heart a patchy Cx43 protein expression pattern was reported suggesting 20 It is possible that the patchy Cx43 staining pattern observed in the myocardial tissue from the Cx43E42K victim results from poor quality of necropsy tissue.…”
Section: Discussionsupporting
confidence: 82%
“…gap junctions, adherens junctions and desmosomes— that enable electro-mechanical coupling [70]. Connexin-43 is the predominant cardiac gap junction protein.…”
Section: Cardiac Cell Maturitymentioning
confidence: 99%
“…Connexin-43 is the predominant cardiac gap junction protein. Gap junctions are clusters of closely-packed transmembrane intercellular channels that enable rapid propagation of the action potential by permitting the movement of low molecular weight materials between cells [70] (Figure 1C). N-cadherin is an important adherens junction protein.…”
Section: Cardiac Cell Maturitymentioning
confidence: 99%
“…N-cadherin expression and localization at cell-cell contacts is associated with increased stability of β-catenin and decreased expression of α-SMA (Xu et al, 2012). CFs form N-cadherin-mediated interactions with CMs, which influences CM structure and contractility during development, normal function and disease (Chopra et al, 2011;Kudo-Sakamoto et al, 2014;Vreeker et al, 2014). In a recent study, N-cadherin bonds between CFs and CMs were shown to dynamically deform CM membranes in response to MyoFB contraction and induce a measurable slowing of CM conduction velocity (Thompson et al, 2014).…”
Section: Cadherins Sense Intercellular Forcesmentioning
confidence: 99%